NON-STANDARD CONTROL MODES OF ASYMMETRICAL SIX-PHASE POWER CONVERSION SYSTEMS WITH SYNCHRONIZED PWM - Oleschuk V.I.; Prudyak R.; Sizov A.S. (Problems of the Regional Energetics)
Novel method of synchronized space-vector pulsewidth modulation (PWM) has been developed and disseminated for control of asymmetrical six-phase systems. It has been shown, that application of the proposed method provides continuous synchronization of the output voltage of six-phase converters during the whole control range for both standard and non-standard control modes of power conversion systems.